Sensitivity of Speech Output to Delayed Auditory Feedback in Primary Progressive Aphasias - Hardy, Chris J. D.; Bond, Rebecca L.; Jaisin, Kankamol; Marshall, Charles R.; Russell, Lucy L.; Dick, Katrina; Crutch, Sebastian J.; Rohrer, Jonathan D.; Warren, Jason D. (Frontiers in Neurology, 2018)
Delayed auditory feedback (DAF) is a classical paradigm for probing sensori-motor interactions in speech output and has been studied in various disorders associated with speech dysfluency and aphasia. However, little information is available concerning the effects of DAF on degenerating language networks in primary progressive aphasia: the paradigmatic ‘language-led dementias’. Here we studied two forms of speech output (reading aloud and propositional speech) under natural listening conditions (no feedback delay) and under DAF at 200 msec, in a cohort of 19 patients representing all major primary progressive aphasia syndromes versus healthy older individuals and patients with other canonical dementia syndromes (typical Alzheimer’s disease and behavioural variant frontotemporal dementia). Healthy controls and most syndromic groups showed a quantitatively or qualitatively similar profile of reduced speech output rate and increased speech error rate under DAF relative to natural auditory feedback. However, there was no group effect on propositional speech output rate under DAF in patients with nonfluent primary progressive aphasia and logopenic aphasia. Importantly, there was considerable individual variation in DAF sensitivity within syndromic groups and some patients in each group (though no healthy controls) apparently benefited from DAF, showing paradoxically increased speech output rate and/or reduced speech error rate under DAF. This work suggests that DAF may be an informative probe of pathophysiological mechanisms underpinning primary progressive aphasia: identification of ‘DAF responders’ may open up an avenue to novel therapeutic applications.